Stress-Strain Response Of Full Scale Rubberized Reinforced Concrete Column Under Vertical Load - Mohamed, Nurul Atiqah (Universiti Sains Malaysia, 2017)
This study investigates the behaviour of full scale rubberized reinforced concrete column designed by replacing crumb rubber with fines aggregate. The aim of this study is to investigate the structural response and load carrying capacity of rubberized concrete column subjected to vertical load. This study focuses on the structural performance of short concrete column containing crumb rubber. Fine aggregates were partially replaced by crumb rubber with the size between 0.05 mm to 5 mm by volume. The compression test was carried out to obtain the structural performances of rubberized concrete column at the age of 28 days. The columns were loaded as pinned-end column at both end with no eccentricity. The compressive strength, failure mode of column, elastic modulus and ductility of rubberized concrete column were recorded and analysed. The result shows that the replacement of 15% crumb rubber in fine aggregate reduces the strength of the concrete due to the reduction in concrete density. The rubberized concrete column showed better performance in ductility than normal concrete column.